2023
DOI: 10.3390/ijerph20065187
|View full text |Cite
|
Sign up to set email alerts
|

Going Vegan for the Gain: A Cross-Sectional Study of Vegan Diets in Bodybuilders during Different Preparation Phases

Abstract: Numerous athletes compete at a high level without consuming animal products; although a well-planned vegan diet might be appropriate for all stages of the life cycle, a few elements need to be addressed to build a balanced plant-based diet for an athlete, particularly in bodybuilding, in which muscle growth should be maximised, as athletes are judged on their aesthetics. In this observational study, nutritional intakes were compared in a cohort of natural omnivorous and vegan bodybuilders, during two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…The protein recommendations used in this study align with recommendations for maximal muscular development in young, healthy adults [43]. They align with existing guidelines for athletes following plant-based diets [74] and corroborate evidence that athletes undertaking RET while following completely plant-based diets meet protein requirements for maximal gains in muscle mass and strength [40,75,76]. Our study calculated protein intakes of 1.8 g/kg/day, which exceeds the mean intake levels of 1.6 g/kg/day required to maximize RET-induced gains in muscle mass and strength in healthy adults [47].…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The protein recommendations used in this study align with recommendations for maximal muscular development in young, healthy adults [43]. They align with existing guidelines for athletes following plant-based diets [74] and corroborate evidence that athletes undertaking RET while following completely plant-based diets meet protein requirements for maximal gains in muscle mass and strength [40,75,76]. Our study calculated protein intakes of 1.8 g/kg/day, which exceeds the mean intake levels of 1.6 g/kg/day required to maximize RET-induced gains in muscle mass and strength in healthy adults [47].…”
Section: Discussionsupporting
confidence: 75%
“…However, the dietary assessment methods used in these studies, which consisted mainly of 3- to 7-day food diaries, are known to underestimate energy intake [ 73 ]. Moreover, a recent cross-sectional study by Amatori and colleagues (2023) reported a mean calorie intake of 2632 kcal/day among bodybuilders following completely plant-based diets [ 40 ]. This study estimated food intake using a digital food diary, which may also underestimate energy intake [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations